Empowerment of the older adults in the context of Chinese culture: an evolutionary concept analysis - Zhang, Shibo; Li, Junfeng; Zou, Jingjie; Ai, Yating; Qin, Siqi; Xiao, Xixi; Hu, Hui; Wang, Yuncui (Frontiers in Psychology, 2023)
Background: With the increasing focus on addressing the challenges of aging, researchers have begun to recognize the potential impact of empowering older individuals in addressing retirement issues. However, within different cultural contexts, there still needs to be a more precise analysis regarding the definition of empowering older individuals.Objective: To define and analyze the concept of empowering older individuals within the cultural context of China. Method: Using Rodgers' concept analysis approach, a search was conducted in five databases (PubMed, Web of Science, China National Knowledge Infrastructure, Wan fang Data, and VIP Chinese Journal Platform) for studies on empowering older individuals from the time the databases were established until February 2023. The main disciplines involved in the search included nursing, medicine, and public health. Results: Out of the 7028 studies, 50 articles met the inclusion criteria. The identified attributes are as follows: support system, belief change, and behavioral autonomy. The antecedents were grouped into four categories: physical obstacles, psychological concerns, personal needs and external challenges. The consequences were determined to be improved quality of life, reduced burden of old-age care, gain respect, and self-actualization. Conclusion:Empowering older individuals is a dynamic and evolving concept that involves aligning personal aspirations with appropriate external resources and expressing a certain degree of belief and behavioral change. This study deepens our understanding of empowering older individuals through comprehensive concept analysis, and the identified attributes, antecedents, and consequences of empowering older individuals can be utilized in practice, education, and research.